Digital Encyclopedia of Applied Physics 2009
DOI: 10.1002/3527600434.eap660
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Dynamics in Biomolecules

Abstract: Organisms have evolved a wide variety of mechanisms to utilize and respond to light. In many cases, the biological response is mediated by structural changes that follow photon absorption. These reactions typically occur at femto‐ to picosecond timescales. As the relevant time and spatial resolutions are notoriously hard to access experimentally, molecular dynamics (MD) simulations are the method of choice to study such ultrafast processes. In the simulations, a multiconfigurational quantum mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 126 publications
0
19
0
Order By: Relevance
“…In our implementation, only the QM components of the derivative coupling vectors are used in QM/MM GTSH dynamics simulations because the MM components are expected to be very small; in addition, they are available only numerically so that their evaluation is expensive. Similar approximations have been used in previous QM/MM FSSH applications 7,12,14,24,[76][77][78] and in QM/MM optimizations of conical intersections. 79,80 In the same spirit, the spin-orbit couplings between electronic states I and J with different spin are determined from the QM wavefunctions obtained in the QM/MM calculations with electronic embedding,…”
Section: Qm/mm Implementationmentioning
confidence: 90%
See 1 more Smart Citation
“…In our implementation, only the QM components of the derivative coupling vectors are used in QM/MM GTSH dynamics simulations because the MM components are expected to be very small; in addition, they are available only numerically so that their evaluation is expensive. Similar approximations have been used in previous QM/MM FSSH applications 7,12,14,24,[76][77][78] and in QM/MM optimizations of conical intersections. 79,80 In the same spirit, the spin-orbit couplings between electronic states I and J with different spin are determined from the QM wavefunctions obtained in the QM/MM calculations with electronic embedding,…”
Section: Qm/mm Implementationmentioning
confidence: 90%
“…[1][2][3] It is attractive because it is easy to implement and offers an intuitive interpretation, and it has thus been adopted by many groups. [4][5][6][7][8][9][10][11][12][13][14][15][16] It has been applied to study many ultrafast photophysical and photochemical processes in the gas phase and the condensed phase. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Despite the growing popularity and success of the trajectory-based FSSH method, it remains approximate and has some well-known drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the gradient of the excitation energy obtained above is added to that of the ground-state energy (22) where D μνσ is a ground-state density matrix element and μνσ , κλτ is the DFT two-particle density matrix…”
Section: A Sfdft/efp1 Methodsmentioning
confidence: 99%
“…9 Several studies have been reported in which CI points including environmental effects have been located. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Burghardt et al 10,11 have evaluated solvent effects on a CI point within the dielectric continuum model and applied the nonequilibrium free energy formulation to a model protonated Schiff base. Using the reference interaction site model selfconsistent field (RISM-SCF) method, Yamazaki and Kato 12,13 determined the CI points of ethylene, CH 2 NH 2 + , and 9H-adenine in polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Conical intersections are not a single point but a multidimensional seam of 3N−8 degrees of freedom where N is the number of atoms in a system. These conical intersections are usually formed between electronic states with same spatial symmetries and spins, which are defined as seams of the true degeneracy between electronic states.…”
Section: Introductionmentioning
confidence: 99%